Education as an element of integration policy – comparative analysis - Woźniak, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2019)
The aim of the article is to present and evaluate the main activities that support the education of immigrant children in Poland and in selected European countries as well as to compare the models of integration in the field of the education of immigrant children in respective countries. The article uses the following methods: critical analysis of the literature and deductive reasoning techniques. The paper consists of three parts. The first part presents the role of education in integration policy and the objectives of the main models of integration in the area of the education of immigrant children. The second part presents legal regulations and key data relevant to immigrant children in Polish schools. The third part of the article presents integration models in European countries and compares the models of integration in Poland and in other European countries. The research hypothesis is the following: education of immigrant children as an important aspect of the policy of integration is characterised by diversified activities in respective European countries.